Grain characteristics of tephra from the subglacial SILK-LN Katla eruption ~3400 years ago and the subaerial Hekla eruption in 1947 - Edda Sóley Þorsteinsdóttir 1979- (2015)
Diskur fylgir prentaða eintakinu sem er varðveitt í Landsbókasafni íslands - Háskólabókasafni In this project grain size and grain shape characteristics of silicic to intermediate tephra from two volcanoes, Katla and Hekla, are studied. Chemical composition of the tephra is similar but the eruption environment is quite different. The ~3400 years old Katla SILK-LN and the Hekla 1947 tephra layers were studied with respect to grain size changes with distance from the source and their grain characteristics were compared. The main focus was on the finer fraction of the tephra grains. The results show obvious difference both in mean grain size and the fraction of finest particles from the two volcanoes. The Hekla 1947 tephra has significantly higher mean grain size and much lower content of material finer than ≤4 Ф at all distances than in the SILK-LN tephra. The mean grain size of Hekla 1947 decreases more rapidly with distance than that of the SILK-LN tephra. The difference between the two layers regarding grain morphology is very clear. The grains from the Katla tephra are elongated and are even needle shaped, but the grains from the Hekla tephra are more equant. A pilot study on silicic Katla layers (SILK) formed between 2800-8100 years ago was undertaken to examine whether their grain characteristics had changed with time and in such a case could indicate changes in eruption environment when the SILK layers formed. Neither mean grain size nor grain morphology of the SILK tephra layers changed with time but the second oldest tephra layer A11 stands out regarding the grain morphology not having the typical elongated grains and resembling more the 1947 Hekla tephra. Verkefnið fjallar um kornastærðareinkenni súrra til ísúrra gjóskulaga frá tveim eldfjöllum, Kötlu og Heklu. Efnasamsetning gjóskunnar er svipuð en gosumhverfið er ólíkt. Tvö gjóskulög, Kötlulagið SILK-LN um 3400 ára gamalt og Heklulagið úr gosinu 1947 voru skoðuð með tilliti til kornastærðarbreytinga með fjarlægð frá upptökum og kornalögunareinkenni ...